Efficiency Test and Economic Analysis of Seeder for Papaya-sowing Tray - Piyapong Sriwongras; Petr Dostál (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2014)
The objective of this project was to develop the seeder for sowing tray to reduce the labor cost and the operation time for preparing sowing tray. Papaya seeds were selected for test on this machine. The sowing tray used for test has 60 cells per one tray. The dimensions of seeder developed have a width of 1,044 mm, a length of 679 mm. and a height of 1,348 mm. The important components of machine consisted of seed hopper, seed metering device, seed releasing units, soil compressing units and depth controlling units. The seed metering device was established by plastic sheet. The plastic rods cut into keyway along its axis for keeping seeds were inserted into the seed metering device in order to convey the seeds from the seed hopper to the flexible tube. The flexible tubes brought the seeds into seed releasing units located under the part of seed metering device in order to drop the seeds 1–2 seeds per cell of sowing tray. The seed metering devices were set 3 units, 1 unit for releasing seeds on 20 cells of sowing tray, on the seeder frame. Chain drive mechanism was set to drive the system for releasing seeds on sowing tray. The efficiency test of releasing seed on sowing tray of this seeder was equal to 79%. For operation time of releasing seeds on sowing tray, Comparing between this seeder and human hand found that the sowing by the seeder was 7.88 times quicker than the sowing by human hand. In parts of economic analysis of seeder, breakeven point, payback period and benefit cost ration were considered for economic analysis. Their results found that were 152,050 trays, 0.03 year and 3.05 respectively. Therefore, the seeder of papaya sowing tray developed is suitable for using in local farmers in Thailand.